ANALYZING THE EFFECTS OF WATER, AIR, AND SALTWATER COOLANTS ON THE TENSILE STRENGTH & HARDNESS OF AISI 1045 STEEL WELDED WITH METAL INERT GAS - Muhammad Hariz Dedy Sayogi; Jefri Aldo; Lia Agustina; I Made Susanto (Jurnal Dinamika Vokasional Teknik Mesin, 2026)
This study aims to analyze the effect of cooling media variations (air, water, and salt water) on the mechanical properties of AISI 1045 medium carbon steel welded using the Metal Inert Gas (MIG) method. The experimental method was used with steel specimens in the form of plates which were then tested for tensile strength in accordance with the ASTM E8 standard and tested for hardness. The results of the study show that cooling with air produces the highest tensile strength (35.59 Kgf/mm²) due to the formation of ductile pearlite and ferrite microstructures. Cooling with water produced moderate tensile strength (34.42 Kgf/mm²), while cooling with salt water produced the lowest tensile strength (22.34 Kgf/mm²) due to the formation of hard but brittle martensite. Conversely, the highest hardness value was obtained with saltwater cooling (386.20 HV in the HAZ), followed by water, and the lowest with air. In general, slow cooling increases ductility and tensile strength, while rapid cooling increases hardness but decreases ductility. These findings emphasize the importance of selecting the appropriate cooling medium according to application requirements, whether the emphasis is on tensile strength or material hardness.